2019
DOI: 10.1002/adma.201905711
|View full text |Cite
|
Sign up to set email alerts
|

A Nacre‐Inspired Separator Coating for Impact‐Tolerant Lithium Batteries

Abstract: The commercial ceramic nanoparticle coated microporous polyolefin separators used in lithium batteries are still vulnerable under external impact, which may cause short circuits and consequently severe safety threats, because the protective ceramic nanoparticle coating layers on the separators are intrinsically brittle. Here, a nacre‐inspired coating on the separator to improve the impact tolerance of lithium batteries is reported. Instead of a random structured ceramic nanoparticle layer, ion‐conductive porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Up to now, a variety of techniques have been developed to attempt solving LMB safety issues, including structured anode [7][8][9][10], artificial solid electrolyte interphase (SEI) [11,12], electrolyte additive [13,14], high salt concentration of electrolyte [15,16], solid-state electrolyte [17,18] and separator modification [19][20][21][22][23][24][25][26][27][28]. Although these efforts improve LMB safety with varying degrees, most work only focus on a single aspect at a time.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a variety of techniques have been developed to attempt solving LMB safety issues, including structured anode [7][8][9][10], artificial solid electrolyte interphase (SEI) [11,12], electrolyte additive [13,14], high salt concentration of electrolyte [15,16], solid-state electrolyte [17,18] and separator modification [19][20][21][22][23][24][25][26][27][28]. Although these efforts improve LMB safety with varying degrees, most work only focus on a single aspect at a time.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Song et al 84 reported a nacre‐inspired separator via fabricating multilayered coating consisted of porous aragonite platelets (PAPs) on both sides of microporous polyethylene (PE) separator (noted as PAPCS), as shown in Figure 5(A). The structure of this PAPCS is “brick‐and‐mortar” like, while ceramic nanoparticle‐coated separator (CNCS) shows pellet‐like structure (Figure 5(B)).…”
Section: Interfacial Instability Between Electrode and Electrolyte: Pmentioning
confidence: 99%
“…(A) Schematic of PAPCS fabrication; (B) cross‐sectional SEM images of PAPCS and ceramic nanoparticle‐coated separator (CNCS); and (C) residual velocity (V)‐time (t) curves for the PAPCS and CNCS at the impact velocity of 5 m s −1 . Reproduced with permission: Copyright 2019, Wiley‐VCH 84 . (D) Schematic of M‐P/P coated separator fabrication; (E) photographs of the Celgard separator, (P/P) 10 , and (M‐P/P) 10 coated separators before and after thermal treatment for 2 min at 150°C; (F) contact angle measurement of the Celgard separator, (P/P) 10 , and (M‐P/P) 10 coated separators; and (G) photographs of the diffusion experiment with the Celgard separator and (M‐P/P) 10 coated separator.…”
Section: Interfacial Instability Between Electrode and Electrolyte: Pmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In particular, lithium ion batteries have dominated the energy market since their commercialization in 1990s, ranging from portable electronics, electric vehicles, and smart energy storage. [9][10][11][12][13] However, the reserves of lithium resources in the earth's crust are limited and distributed unevenly, which will lead to intrinsic high price with the increasing requirement of LIBs, limit their development for large-scale application.…”
Section: Introductionmentioning
confidence: 99%